Cover, Content, and Editorial Note from Borneo J Pharm Vol. 6 No. 1 February 2023 - Chief Editor of Borneo J Pharm (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published in February 2023. This edition contains ten articles: Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Clinical-Community Pharmacy, and Management Pharmacy. This edition includes writings from six countries: Anguilla, Costa Rica, India, Indonesia, Nigeria, and Russian Federation. The authors come from several institutions, including Universitas Islam Indonesia, Sekolah Tinggi Ilmu Farmasi Riau, Universitas Andalas, Pyatigorsk Medical and Pharmaceutical Institute, Universitas Muhammadiyah Banjarmasin, Universitas Tanjungpura, Universidad de Costa Rica, Ahmadu Bello University, Akademi Farmasi Surabaya, Universitas Airlangga, Universitas Sumatera Utara, Sekolah Tinggi Ilmu Kesehatan Senior Medan, Prathima Institute of Medical Sciences, Saint James School of Medicine, Vaagdevi Degree and PG College, and Vydehi Institute of Medical Science and Research Center. Editorial boards are fully aware that there are still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repetoire in this issue. We hope that all parties, especially the contributors, could re-participate for the publication in the next edition on May 2023. Wassalamu’alaikum Wr. Wb.